2021
DOI: 10.3390/microorganisms9040849
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mutations That Confer Fluoride Resistance Modify Gene Expression and Virulence Traits of Streptococcus mutans

Abstract: Fluoride is an inorganic monatomic anion that is widely used as an anti-cariogenic agent for the control of caries development. The aims of this study were to identify the mutated genes that give rise to fluoride-resistant (FR) strains of the cariogenic pathogen Streptococcus mutans and explore how genetic alterations in the genome of an S. mutans FR strain optimize the metabolism(s) implicated in the expression of virulence-associated traits. Here, we derived an S. mutans FR strain from a wild-type UA159 stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
3
10
0
Order By: Relevance
“…The lower ratio of the fluoride-resistant strain within the dual-species biofilm without NaF compared to its wild strain might be partly attributed to the slow growth rate of the fluoride-resistant strain in our study (data not shown). The slow growth rate of the fluoride-resistant strain was consistent with previous reports, which might have resulted from bacterial-deficient carbohydrate uptake ( Liao et al., 2015 ; Lee et al., 2021 ). The ratio of either S. mutans or its fluoride-resistant dual-species was raised without NaF with the development of biofilm when compared between 24 and 48 h, which was confirmed by FISH and qRT-PCR.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The lower ratio of the fluoride-resistant strain within the dual-species biofilm without NaF compared to its wild strain might be partly attributed to the slow growth rate of the fluoride-resistant strain in our study (data not shown). The slow growth rate of the fluoride-resistant strain was consistent with previous reports, which might have resulted from bacterial-deficient carbohydrate uptake ( Liao et al., 2015 ; Lee et al., 2021 ). The ratio of either S. mutans or its fluoride-resistant dual-species was raised without NaF with the development of biofilm when compared between 24 and 48 h, which was confirmed by FISH and qRT-PCR.…”
Section: Discussionsupporting
confidence: 91%
“…At present, there is no unified conclusion about the variation in acid production ability of wild-type S. mutans compared with fluoride-resistant S. mutans . Some studies found that fluoride-resistant S. mutans had a weaker acid production ability, while others found it to be stronger when compared to its related wild strain, and further studies found that there was no significant difference between these two strains ( Eisenberg et al., 1985 ; Van Loveren et al., 1991 ; Hoelscher and Hudson, 1996 ; Cai et al., 2017 ; Lee et al., 2021 ). This diversity might be derived from different culture conditions and bacterial strains and induced by fluoride-resistant strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, murB, htrA, SMU.753, and spxA regulated by LiaSR and SMU.862 regulated by BceRS were also upregulated. Lee et al suggested that genetic mutations in S. mutans fluoride-resistant strains resulted in the reduced activity of PTSs, such as ManXYZ and ManLMN, which strongly affect carbon inflow and energy production via the central carbon metabolism, whereas the upregulation of MsmEFGK and MalXFGK can overcome the restricted carbon flow (Lee et al, 2021). Transcriptomic analyses demonstrated that diterpenoids downregulated genes associated with most PTSs.…”
Section: Discussionmentioning
confidence: 99%